Evanescence and Tragic Beauty An Existential Reading of Yukio Mishima’s The Temple of the Golden Pavilion (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
Yukio Mishima's novel The Temple of the Golden Pavilion is one of the most enigmatic texts in world literature. Narrated in the first-person and with a wealth of psychological details about the narrator's past, the novel has, understandably, attracted the attention of psychoanalysts. Psychoanalytic readings of the text, however, have worked to the principle that the protagonist's actions in the present can be explained by a reference to his past. The present paper reverses this hermeneutic strategy: it focuses on the protagonist's freedom-towards-the-future. What follows, then, is an existential reading of one man's obsessions, as he asserts his freedom and confronts the boundary situations of impermanence and human sexual desire.
Keywords: Freedom; boundary situation; impermanence; sexuality; world-design